The Controlling Role of Da'wah Management in Teaching Activities at the Asshiddiqiyah Islamic School 6 Serpong - Abdul Muizz AM (FDIK IAIN Padangsidimpuan, 2022)
Service management is process management, namely the management that regulatesand controls service processes, so that the mechanism of service activities can run in anorderly, smooth, precise manner target and satisfy the party to be served. servicemanagement theory is very appropriate to be used in research which aims to know andunderstand how services at Islamic boarding school as-shiddiqiyah 6 serpong Collectingdata in this study using the methodobservations, interviews, and documentation, withdeductive analysis, sampling technique using porposive sampling. Data The primarysources in this study include the leader of the lodge, administrators,and 3 students whoexcel. And secondary data are books as well as several references that are relevant to theresearch title. Method of collecting data; interviews (interviews), observations anddocumentation. After the data is collected, data analysis is carried out using qualitativemethods. Research result; management Services at the Asshiddiqiyah Islamic BoardingSchool 6 Serpong include administrative services, goods and services services (services forproviding student needs, learning process services) teaching, health services, studenttelephone services).The results of this study are services in Islamic boarding schools asshiddiqiyah 6serpong in giving satisfaction done by the staffs are mature enough, as evidenced byAppearance neat employees, comfortable service place Sufficient facilities andinfrastructure, disciplined employees in performing services, employees who provide easeof serving students, good service accessquite good, Using tools in service. the reliability ofthe boarding school is sufficient well evidenced by the accuracy of employees in servingstudents, the standard of service in Islamic boarding schools Asshiddiqiyah 6 serpong isquite good, Expertise the ability of employees who are already good in using service tools. Guarantees provided by the cottage Asshiddiqiyah Islamic Boarding School 6Serpong are as follows, Guarantee in Administrative Services and services of goods andservices. empathy carried out by the Asshiddiqiyah Islamic boarding school 6 serpong isgood enough in prove it with good communication with students as well as providingcounseling guidance (BK) teachers with the goal is to solve problems faced by students.